De Pentamerone: De beroemde verzameling Italiaanse volksverhalen - Basile, Giambattista 1583-1632; Valkhoff, R. (Amsterdam Meulenhoff, 1960)
'The Pentamerone', subtitled 'Lo cunto de li cunti' ("The Tale of Tales"), is a seventeenth-century Neapolitan fairy tale collection by Italian poet and courtier Giambattista Basile. The stories were collected by Basile and published posthumously in two volumes by his sister Adriana in Naples, Italy, in 1634 and 1636 under the pseudonym Gian Alesio Abbatutis. These stories were later adapted by Charles Perrault and the Brothers Grimm, the latter making extensive, acknowledged use of Basile's collection. Examples of this are versions of Cinderella, Rapunzel, Puss in Boots, Sleeping Beauty, and Hansel and Gretel.
Originally published in 1634-6
Keywords: 17th Century (1601-1700); Fairy tale; Short story; Naples (Italy)